GIS-Based exposure assessment of primary roads and bridges to flood and landslide hazards in Central Java, Indonesia - Kushari, Berlian; Ramli, Muhammad Isran; Bakri, Bambang; Arsyad, Ardy (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2026)
The continuity of road transportation services is always threatened by flash flood and landslide in Central Java Province that is always exposed to disaster. This study proposes a province-wide GIS-based assessment to determine the most vulnerable road sections and bridges to these hazards. Road and bridge inventories were overlaid on the official BNPB hazard maps by using ArcGIS, and exposure levels were quantified by the length of the road segments and the number of bridges crossing the low-, medium-, and high-hazard areas. The definition of hazard used in this study is the spatial potential of occurrence, not to be understood as a measure of risk of network vulnerability. The results indicate that flash flood exposure is not limited to lowland corridors, but is also prevalent in upland corridors, and that there are significant exposures along riverine systems. In contrast, landslide exposure is more spatially concentrated along upland corridors associated with steep terrain. There are several corridors that are identified as multi-hazard hotspots, such as Karang Pucung – Wangon, Bumiayu – Salem and Kutoarjo – Bruno – Wonosobo. Overall, this study offers explicit spatial information regarding exposure to hazards of the primary road network, which can serve as a basis for prioritization of mitigation, monitoring, and further connectivity-based hazard vulnerability analysis.